Back pain: Detrimental Consequences of Monsoon on Health - Muhammad Sadiq; Dawani, Gautam; Masroor, Muhammad Moiz (Journal of the Pakistan Medical Association, 2023)
Dear Editor, Karachi, the economic hub of Pakistan, is home to a sizable workforce and members of the lower and middle classes. Due to their low cost, two-wheelers are the most preferred mode of transport especially by the workforce. In Karachi, there are reportedly more than 1 million motorcycles. By 2030, this number is anticipated to increase 3 times (1). Karachi’s poorly maintained road infrastructure has been severely damaged by the monsoon spells and the consequent flooding (2). Accumulation of water on roads has led to the formation of craters, potholes and washing away of road carpeting. This battered condition of roads has become a torment for commuters, especially motorcyclists. Multiple reports suggest a relationship between driving on bumpy roads and pathologies related to the back. An article published in The News International reported that more than 50% of the young bikers suffer from backache because of constant strain on backbone and surrounding tissues (3). The disorders caused by the deteriorating condition of roads include but are not limited to slipped discs, cervical spondylitis, and whiplash injuries (4). In addition it may potentially aggravate certain musculoskeletal disorders, for example arthritis (5). The increasing incidence of these pathologies is worrisome, and it is burdening the already overwhelmed healthcare facilities. In addition to this, since there is a lack of awareness, many people do not consult a doctor timely and delayed diagnosis can cause permanent damage. Chronic back pain patients also suffer from psychosocial distress. Hence awareness campaigns should be held, which can be complemented by widespread screening of these pathologies. Motorcyclists should be advised regular exercise, physiotherapy, and medicated lumbosacral support during riding which can decrease back sprain. People who have already been diagnosed with these disorders should also be provided with economical rehabilitation facilities to improve their lifestyle. Lastly, research should be conducted to find out the incidence and prevalence of other disorders related to bumpy roads, and to find out economic prevention and treatment methods.